2019
DOI: 10.1186/s40425-019-0523-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies as biomarker candidates for response and survival to checkpoint inhibitors in melanoma patients

Abstract: Background: Long-term survival of stage IV melanoma patients has improved significantly with the development of immune checkpoint inhibitors (CIs). Reliable biomarkers to predict response and clinical outcome are needed. Methods: We investigated the role of melanoma-associated antibodies as predictive markers for CI therapy in two independent cohorts. In cohort 1, a prospective study, we measured specific antibodies before treatment, after one week and after six to nine weeks of treatment. Cohort 2 consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 55 publications
1
50
0
1
Order By: Relevance
“…MART-1, which is encoded by MLANA, contains a peptide that is presented by MHC-I and efficiently recognized by T cells [38]. In addition, other pigmentation markers including TYR and DCT serve as melanoma antigens [39]. Accordingly, when melanomas are driven into dedifferentiation, they can more easily escape T cell control [11].…”
Section: Discussionmentioning
confidence: 99%
“…MART-1, which is encoded by MLANA, contains a peptide that is presented by MHC-I and efficiently recognized by T cells [38]. In addition, other pigmentation markers including TYR and DCT serve as melanoma antigens [39]. Accordingly, when melanomas are driven into dedifferentiation, they can more easily escape T cell control [11].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of B cell mediated cytotoxicity via granzyme B and TRAIL has been shown in hepatocellular carcinoma ( 83 ). IgG class antibodies have been found to be tumor-specific, and this has been reported in melanoma ( 75 ) and other cancer types and has been correlated with a favorable prognosis ( 84 87 ).…”
Section: Antibody Responses In Melanomamentioning
confidence: 88%
“…One study showed that patients with GC had a worse prognosis if they were positive for more than 2 antibodies in the panel of TP53, heat shock protein 70, p90, HCC-22-5, KM-HN-1, and peroxiredoxin VI ( 38 ). Another study showed that high levels of antibodies against TRP1/TYRP1, TRP2/TYRP2, gp100, and Melan/MART1 may be useful metastatic biomarkers for melanoma ( 41 ). Therefore, the serial serum samples from 23 patients with GAC were detected to investigate the temporal changes of these autoantibodies in this study.…”
Section: Discussionmentioning
confidence: 99%